2017
DOI: 10.1016/j.jcs.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic sorghum with suppressed synthesis of kafirin subclasses: Effects on flour and dough rheological characteristics

Abstract: Arising from work showing that conventionally bred high protein digestibility sorghum types have improved flour and dough functionality, the flour and dough properties of transgenic biofortified sorghum lines with increased protein digestibility and high lysine content (TG-HD) resulting from suppressed synthesis of several kafirin subclasses, especially the cysteine-rich γkafirin, were studied. TG-HD sorghums had higher flour water solubility at 30 o C (p <0.05) and much higher paste viscosity (41% higher) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The decline of τ indicates that dough opposes less resistance as the fermentation time increases, meaning that doughs start exhibiting a decreased elastic behavior compared to control. This has been discussed in another study where it was found that sourdoughs have lower shear stress values compared to regular doughs [27].…”
Section: Rheology Assaysmentioning
confidence: 83%
“…The decline of τ indicates that dough opposes less resistance as the fermentation time increases, meaning that doughs start exhibiting a decreased elastic behavior compared to control. This has been discussed in another study where it was found that sourdoughs have lower shear stress values compared to regular doughs [27].…”
Section: Rheology Assaysmentioning
confidence: 83%
“…Several studies have opted to use Confocal Laser Scanning Microscopy (CLSM) as an alternative to SEM; this technique uses the emitted fluorophores of a sample after a laser scan to generate the image [ 112 ]. Taylor et al used this technique to show the fibril formation of zein and kafirin resins, while Elhassan et al used it to investigate the internal structure of kafirin doughs, an unavailable application for SEM [ 63 , 71 ]. Since both microscopies techniques can study the microstructure of a sample, the election of equipment would depend on the information needed.…”
Section: Methodologies For the Measurements Of The Gluten Substitumentioning
confidence: 99%
“…The rheometer is used to comprehend the dough rheological effects of a modification on final products [ 67 ]. This equipment works by applying a rotational or sinusoidal (oscillatory) shear deformation on a sample and measuring the resulting stress response, which can be used to study the viscoelastic moduli (G’ and G”) of gluten-free bread [ 67 , 69 , 71 , 115 ]. Since both techniques obtain the same information, the election would depend on the type of material studied.…”
Section: Methodologies For the Measurements Of The Gluten Substitumentioning
confidence: 99%
See 2 more Smart Citations